Tracing the Observed Causal Impact of Diminishing Summer Sea‐Ice Concentration on the Atlantic Meridional Overturning Circulation - Denis‐Răducu Nichita; Irina Dubet; Mihai Dima; Monica Ionita (Geophysical Research Letters, 2025)
Abstract The Atlantic Meridional Overturning Circulation (AMOC) is a crucial component of the global climate system and is believed to have slowed down in recent decades. While models indicate that anthropogenic Arctic sea‐ice melting drives this slowdown, observational evidence for this connection remains lacking, leaving the attribution of the AMOC decrease unresolved. In this study, we present causal observational evidence, beyond correlation, that the recent weakening of the AMOC observed in its sea surface temperature (SST) fingerprint is influenced by the decline in summer Arctic sea‐ice concentration over the past century, particularly between the 1950s and 1980s, concurrent with the Great Salinity Anomaly. Using two methods—Convergent Cross Mapping from dynamical systems theory and Information Flow from information theory—we demonstrate that modes of AMOC variability are influenced by sea‐ice melting. The AMOC slowdown and its modes exhibit a causal lag of 1–3 decades relative to sea‐ice melting, aligning with model predictions.